Poljubnost in standardiziranost anketne konverzacije - Uhan, Samo (Teorija in praksa, 1999)
A distinctive feature of public opinion research is that survey interview is considered to be specific kind of conversation or social activity involving people who are not acquainted which is therefore governed by general conversational rules. However participation in the survey interview is governed by particular methodological rules. In consenting to the interview, the respondent accepts a specific kind of social interaction - agreeing to take part in a research whose ultimat purposes are not known to him and what at the same time requires adherence to the resercher instructions. Strict observance of the instructions does not eliminate the methodological problems. Namely, for the respondent the semantic comprehension of the researcher's directions is insufficient. The respondent is forced to shape the excess meaning of information available to him. It is assumed that respondent uses the information, he manages to extract from the conversation with the interviewer. Accordingly, we have to abandon the belief that the instrument is a neutral stimulus which provokes a reaction that has only to be recorded objectively.
Keywords: javno mnenje; družboslovno raziskovanje; anketa; kontekstualna analiza; standardi; communication; komuniciranje